Deletion of Prdm8 impairs development of upper‐layer neocortical neurons. (18th August 2015) - Inoue, Mayuko; Iwai, Ryota; Yamanishi, Emiko; Yamagata, Kazuyuki; Komabayashi‐Suzuki, Mariko; Honda, Aya; Komai, Tae; Miyachi, Hitoshi; Kitano, Satsuki; Watanabe, Chisato; Teshima, Waka; Mizutani, Ken‐ichi
<x xml:space="preserve">Abstract</x> Upper‐layer (UL) neocortical neurons are the most prominent distinguishing features of the mammalian neocortex compared with those of the avian dorsal cortex and are vastly expanded in primates. However, little is known about the identities of the genes that control the specification of UL neurons. Here, we found that Prdm8, a member of the PR (PRDI‐BF1 and RIZ homology) domain protein family, was specifically expressed in the postnatal UL neocortex, particular those in late‐born RORß‐positive layer IV neurons. We generated homozygous Prdm8 knockout (Prdm8 KO) mice and found that the deletion of Prdm8 causes growth retardation and a reduced brain weight, although the brain weight‐to‐body weight ratio is unchanged at postnatal day 8 (P8). Immunohistochemistry showed that the relative UL thickness, but not the thickness of the deep layer (DL), was significantly reduced in Prdm8 KO mice compared with wild‐type (WT) mice. In addition, we found that a number of late‐born Brn2‐positive UL neurons were significantly decreased in Prdm8 KO mice. To identify genes regulated by Prdm8 during neocortical development, we compared expression profiling analysis in Prdm8 KO and WT mice, and identified some candidate genes. These results suggest that the proper expression of Prdm8 is required for the normal development and construction of UL neurons in the mammalian neocortex.